2019
DOI: 10.1186/s13104-019-4796-9
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and alcohol use disorder among prisoners in Jimma Zone correctional institution, Southwest Ethiopia: a cross-sectional study

Abstract: ObjectiveTrauma exposure and alcohol use are closely related, and large proportion of trauma-exposed individuals use alcohol. The data presented in this paper were obtained as part of a study on substance use disorder and associated factors among prisoners in the correctional institution in Jimma, Southwest Ethiopia. Therefore, in this study we examined comorbidity of traumatic life experiences and alcohol use disorder in inmates of correctional institution in Jimma, Southwest Ethiopia.ResultsThe overall preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…On the other hand, our study showed a much higher prevalence compared to many of the previous reports from different parts of the world which reported prevalence rates ranging from 13.7 to 51.0% [16, 20, 31-33, 38, 40, 41, 43, 46, 47]. Our finding is also higher compared to a previous prison based studies in Ethiopia which reported a 34.0% [12], and 40.1% [53] prevalence for alcohol use and AUD, respectively. Our finding is also much higher compared to the results of a meta-analysis on the epidemiology of alcohol use in Ethiopia which reported a 24% pooled prevalence of current use [52].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…On the other hand, our study showed a much higher prevalence compared to many of the previous reports from different parts of the world which reported prevalence rates ranging from 13.7 to 51.0% [16, 20, 31-33, 38, 40, 41, 43, 46, 47]. Our finding is also higher compared to a previous prison based studies in Ethiopia which reported a 34.0% [12], and 40.1% [53] prevalence for alcohol use and AUD, respectively. Our finding is also much higher compared to the results of a meta-analysis on the epidemiology of alcohol use in Ethiopia which reported a 24% pooled prevalence of current use [52].…”
Section: Discussioncontrasting
confidence: 75%
“…AUDIT is reported to be suitable for the prison population in non-English speaking communities [62]. The Amharic version of AUDIT was adapted and used in Ethiopia previously to assess AUD in many published works [53,[63][64][65][66]. This tool assesses a one-year prevalence of AUD.…”
Section: Assessment Of Alcohol Use Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 The data presented in this paper were obtained from the study on psychopathy and associated factors among newly admitted prisoners in a correctional institution located in Bench Shako and West Omo zone correctional institution, Mizan Aman, Ethiopia. 27 Even though substance use disorder, association between alcohol and trauma, association between psychopathy and khat abuse, and psychopathy and associated factors among prisoners in Ethiopia were well established [31][32][33][34] up to date, the potential association between post-traumatic stress disorder and trauma exposure with problematic khat use among prisoners has not been investigated in our country Ethiopia, or elsewhere. Therefore, the aim of this study was to assess the association between life time trauma exposure and post-traumatic stress disorder with khat use disorder among newlyadmitted prisoners in Bench Shako and West Omo zone correctional institution, Mizan Aman, Ethiopia.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies found increased rates of depression, posttraumatic stress disorder (PTSD), or common mental disorders (CMD) among khat users [e.g., ( 17 19 )]. Studies with representative samples from Jimma town revealed a prevalence of CMD among the general population of between 25.8 and 33.6% ( 20 , 21 ) and among medical students of 35.2% ( 16 ); in all three studies, CMD was positively associated with khat use.…”
Section: Introductionmentioning
confidence: 99%